CT‐Based Classification of Acute Cerebral Edema: Association with Intracranial Pressure and Outcome. Issue 5 (28th May 2020) - Lietke, Stefanie; Zausinger, Stefan; Patzig, Maximilian; Holtmanspötter, Markus; Kunz, Mathias
ABSTRACT: BACKGROUND AND PURPOSE: Brain edema after acute cerebral lesions may lead to raised intracranial pressure (ICP) and worsen outcome. Notwithstanding, no CT‐based scoring system to quantify edema formation exists. This retrospective correlative analysis aimed to establish a valid and definite CT score quantifying brain edema after common acute cerebral lesions. METHODS: A total of 169 CT investigations in 60 patients were analyzed: traumatic brain injury (TBI; n = 47), subarachnoid hemorrhage (SAH; n = 70), intracerebral hemorrhage (ICH; n = 42), and ischemic stroke ( n = 10). Edema formation was classified as 0: no edema, 1: focal edema confined to 1 lobe, 2: unilateral edema > 1 lobe, 3: bilateral edema, 4: global edema with disappearance of sulcal relief, and 5: global edema with basal cisterns effacement. ICP and Glasgow Outcome Score (GOS) were correlated to edema formation. RESULTS: Median ICP values were 12.0, 14.0, 14.9, 18.2, and 25.9 mm Hg in grades 1‐5, respectively. Edema grading significantly correlated with ICP ( r = .51; P  < .0001) in focal and global cerebral edema, particularly in patients with TBI, SAH, and ICH ( r = .5, P  < .001; r = .5; P  < .0001; r = .6, P  < .0001, respectively). At discharge, 23.7% of patients achieved a GOS of 5 or 4, 65.0% reached a GOS of 3 or 2, and 11.9% died (GOS 1). CT‐score of cerebral edema in all patients correlated with outcome ( r = −.3, P = .046). CONCLUSION: The proposed CT‐based grading of extent of cerebral edema significantly correlated with ICP and outcome in TBI, SAH, and ICH patients and might be helpful for standardized description of CT‐images and as parameter for clinical studies, for example, measuring effects of antiedematous therapies.